2020
DOI: 10.3390/ejihpe10040073
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Programs Improve Psychological Flexibility, Mental Health, Well-Being, and Time Management in Academics

Abstract: (1) Background: Occupational stress is high in academia, and is partly related to time pressure. Mindfulness-based programs are known to be effective in reducing stress and increasing well-being. Recent work suggested that these programs may also improve time management. This study tested the effects of a mindfulness-based program on academics’ psychological flexibility, mental health, well-being, and time management. (2) Methods: The study was conducted in a French research department. Participants were offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…Findings in this study that the brief mindfulness intervention improved psychological flexibility and self-compassion are broadly consistent with the result of earlier studies (e.g. Marais et al 2020 ; Wasson et al 2020 ; Weis et al 2021 ). In the study by Marais et al ( 2020 ), the authors reported that a standard eight-week mindfulness-based intervention improved psychological flexibility among the participants.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Findings in this study that the brief mindfulness intervention improved psychological flexibility and self-compassion are broadly consistent with the result of earlier studies (e.g. Marais et al 2020 ; Wasson et al 2020 ; Weis et al 2021 ). In the study by Marais et al ( 2020 ), the authors reported that a standard eight-week mindfulness-based intervention improved psychological flexibility among the participants.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the effects of mindfulness interventions on psychological flexibility and self-compassion, the current study’s findings, as well as the results of previous research (Marais et al 2020 ; Wasson et al 2020 ; Weis et al 2021 ), are important given that promoting such skills is crucial for psychological health and well-being (Marshall and Brockman 2016 ). It becomes even more critical considering the harsh condition of working in a crisis such as the Covid-19 pandemic.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Based on this study regimen it is reasonable to suggest that at least 90 days of exercise training is necessary to stimulate improvements in the elderly endothelial function[61]. A daily brisk walking exercise intervention for 120 days was associated with significantly improved arterial compliance in the older community groups[62]. Regular exercise intervention training is independent of baseline compliance body composition and oxygen capacity[63].…”
mentioning
confidence: 99%